Benin : Staff Assessment of Qualification for the Multilateral Debt Relief Initiative. (Policy Papers; Policy Paper ;, 2005)
Benin reached the completion point under the enhanced HIPC Initiative on March 24, 2003. Staff is of the view that all criteria have been met, and recommends that the Board determine that Benin qualifies for immediate debt relief under the MDRI.